2011
DOI: 10.4028/www.scientific.net/jera.6.75
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varying Distance on Wireless Signal Propagation in Indoor and Outdoor Built Sites

Abstract: The effects of varying distances on wireless signal propagation in indoor and outdoor built sites is presented in this paper. In indoor and outdoor built sites the major RF signal attenuation is due to multi-path interference, signal loss (fading), and non-line of sight signal blockage. A number of mobile communication systems is currently and frequently being used in indoor environments based on IEEE 802.11b standards which is on 2.4GHz frequency ISM band at the rate of 11Mbps. To determine the effects of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…As such, ground electrical parametersrefractivity, reflectivity, conductivity, permittivity and bulging on the radio path, as well as prevailing meteorological conditions, have glaring impact on the transmitting radio waves [3], [4], [5], [6]. Moreso, signals propagated as space waves are influenced by hills, mountains, terrains, multipath interference, non-line of sight blockage, fading and soil electrical parameters within the propagation path [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…As such, ground electrical parametersrefractivity, reflectivity, conductivity, permittivity and bulging on the radio path, as well as prevailing meteorological conditions, have glaring impact on the transmitting radio waves [3], [4], [5], [6]. Moreso, signals propagated as space waves are influenced by hills, mountains, terrains, multipath interference, non-line of sight blockage, fading and soil electrical parameters within the propagation path [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Data transmission in a duct environment is entirely a non-line-of-sight situation. Chomba et al (2011) showed that Wi-Fi signal strength in a non-line-of-sight indoor environment is reduced to less than −100 dBm for a 30-m distance between nodes. In a study by Hashim et al (2014) , it was observed that, for outdoor communication, the Wi-Fi signal lost after 150 m. For indoor communication, the signal lost appeared after only 40 m. In indoor situations, the Wi-Fi area coverage decreases due to obstacles in the indoor environment, which reduce the effectiveness of data transmission and result in path loss.…”
Section: Introductionmentioning
confidence: 99%